Self-medication Practices Among Muslim Youth of Kashmir: An Empirical Study - Bilal Ahmad Bhat; Bilkees Nazir; Ifrah Rashid; Fiba Arif; Qazi Nusrat; Uzma Nazir; Intizar Ahmad (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
In many parts of the world self-medication is a popular practice to treat some common minor diseases in order to save time and money without realizing side effects of self-medication for the patients. We know ‘Over The Counter’ (OTC) drugs are meant for self-medications but their wrong use due to lack of knowledge about medicines can have grave side-effects on patients. In Kashmir the growth in self-medications in Kashmir can be attributed to urge to self-care, feeling of sympathy towards ill family members, deficiency of health services, economic condition, unawareness and easy availability of drugs in medical shops. To treat minor common diseases like fever, cold, cough, diarrhoea etc patients acquire expert advices from family members, neighbours or strangers about medications. Majority of people do not take their illness seriously or avoid Doctor because of busy life, ignoring side effects of self-medication. In Kashmir, it is a common practice in homes to use antibiotics like Co-Amoxyclav 625 and Azithromycin for treating common cold and sharing of prescriptions within the family, using the left over medications for somewhat related symptoms is quite a popular practice. In the present study carried out in Kashmir valley, a survey of the study area was carried out and discussions were held with the elders as well as with medical practitioners. A well-designed validated questionnaire was used to collect the information from 400 youth selected at random from Kashmir on their consent. The data collected from survey was statistically analysed using standard statistical methods. The study revealed that majority of respondents were taking medicine without consulting a Doctor to treat minor ailments. Statistically, it was observed that there was a significant difference in the attitude of male and female respondents towards self medication (P<0.01). The discussion with respondents revealed that they were interested in knowing Islamic ruling about self-medication as in the present world due to lack of patience youth take medicine because of depression and anxiety. Islam allows modern treatment of many diseases like infertility provided it is not against the teaching of Islam and guidance of holy Prophet. Holy Prophet Muhammad (Peace and blessing of Allah be upon him) taught Muslims to pray more in tough times for attaining peace of mind, relief from pain, anxiety and worries. Finally, it was suggested that everyone should avoid self-medication as much as possible and Government should play its role to avoid the selling of banned medicines on medical shops without Doctors prescription